Relações filogenéticas de Toxocara spp. e Toxascaris sp. provenientes de diferentes regiões do mundo - Fava, Natália de Melo Nasser (2017)
The nematodes of the genus Toxocara and Toxascaris are identified, traditionally, based on the morphologic aspects, however the genetic diversity among these parasites is recognized, being an accurate analysis of this variation necessary for the understanding of the biology of these organisms. This work aimed to establish the phylogenetic and phylogeographic relationships among specimens of Toxocara canis, Toxocara cati, Toxocara malaysiensis and Toxascaris leonina and to compare the results given by the morphologic and molecular techniques. In total, 436 helminths adults and four pools of eggs were collected from canids and felines from eight countries. The parasites were analyzed by stereoscopic microscopy, by Polymerase Chain Reaction (PCR) and by Restriction Fragment Length Polymorphism (PCR-RFLP). Primers TOXCOIF3 and TOXCOIR2 were designed in order to amplify 90pb of the mitochondrial gene Cox1, and the PCR-RFLP using the enzyme MseI could discriminate between these four species. The phylogenetic relationships among the isolates were observed in the phylogram and by the genetic variability (phylogenetic distance) rates. Of the 313 parasites adults, from dogs, 309 were identified, by microscopy, as T. canis and four as T. leonina. Of 123 originating from cats 118 were identified as T. cati, four as T. malaysiensis and one as T. leonina. Among the pools the three from lions were identified as T. leonina and that of dog as T. canis. PCR in all analyzed samples (n=440) failed in 3,6%. Of the amplified samples (n=424) 72 were selected to sequencing. With the exception of three samples, two from cats, were characterized as T. canis and one from dog as T. cati, all remaining were identified in agreement with their respective hosts. Of the 424 samples submitted to PCR-RFLP 351 were identified as T. canis/T.leonina, 70 as T. cati and three as T. malaysiensis. This technique presented similar results to sequencing. Homology and genotypic variation were observed within species, being the largest one 6.6%. Phylogeographic relationships within species could be observed by the phylogram. Among the techniques it was observed 9,7% of incongruence in the results between microscopy and sequencing, and 0,9% between microscopy and PCR-RFLP. Between the molecular techniques, it was considered only T. cati and T. malaysiensis which meant 100% of agreement. Based on the findings, of this study, it was concluded that some isolates of the same specie presented intragenotipic variability; Homologous sequences were identified in different countries, suggesting the occurrence of gene flow; The geographic origin was directed related to the genetic variation of the parasites; T. canis and T. cati presented variability rates similar to T. cati and T. leonina; And the three techniques used, herein, showed results that indicate a preference of T. canis, T. cati and T. malaysiensis for certain hosts.